FRI0484 Overall survival and mortality risk factors in takayasu's arteritis: a multicenter study of 318 patients. (12th June 2018) - Mirouse, A.; Comarmond, C.; Biard, L.; Lambert, M.; Mékinian, A.; Kahn, J.-E.; Hachulla, E.; Messas, E.; Resche-Rigon, M.; Caubco, P.; Saadoun, D.
Abstract : Background: Takayasu arteritis (TA) is a rare large vessel vasculitis of unknown origin. Main epidemiological data come from Asia. TA significantly increases morbidity and mortality and there is an unmet need to identify patients with higher complications and mortality risks. Objectives: To report the long term mortality in Takayasu arteritis (TA) and to identify risk factors associated with mortality. Methods: We analysed epidemiological data according to gender and ethnic origins, the causes of death, and the factors associated with mortality in a cohort of 318 patients [median age at diagnosis was 36 25–47 years and 276 (86%) patients were women] fulfilling American College of Rheumatology and Ishikawa criteria of TA. Overall survival and factors associated with death and vascular complications were identified. A prognostic score for death and vascular complications was elaborated based on a multivariate model. Results: In a cohort of 318 patients, men tended to be more frequently smokers (42% vs. 26%, p=0.07), had more frequently cardiac insufficiency (14% vs. 9%, p=0.034), but less frequently aneurysmal lesion (51% vs. 76%, p=0.005). Ethnic origins were Caucasian/White (n=87, 37%), North-Africa (n=73, 31%), Black (n=56, 18%), and other (n=17, 5%). White patients were more frequently smokers and diagnosis was more frequently made after 35 years. Black patients had less frequently a supra-aortic vessels involvement and more frequently a vessel wall thickening at diagnosis (78% vs. 62%, p=0.033). Among 318 TA patients, 16 (5%) died after a median follow-up of 6.1 years. The mean (±SD) age at death was 38 25–47 years with 88% of women. Main causes of death included mesenteric ischemia (n=4, 25%), aortic aneurysm rupture (n=4, 25%), sudden death (n=3, 19%), septic shock (n=3, 19%), pulmonary embolism (n=1, 6%), and cardiogenic shock (n=1, 6%). One, five, and ten years' overall survival were 98.9% [97.8–100], 98.1% [96.4–99.8], and 96.1% [93.4–98.9%], respectively. Factors associated with mortality were ethnic origin (White 9.5% vs. North Africa 7.1% vs. Black 0%, p=0.049), and tobacco smokers (10.8% vs. 4.2%, p=0.002). We define high risk patients for death and vascular complications according to the presence of two of the following factors (i.e a progressive clinical course, thoracic aorta involvement and/or retinopathy) elaborated based on the multivariate model. The probability of death and complication free survival at five years was 78.4% (69.4–88.6) and 51.5% (38.3–69.2) (p=0.001) in the low risk and high risk group, respectively. Conclusions: The overall mortality in our Takayasu cohort was 5% after a median follow-up of 6.1 years. Caucasian and tobacco smokers were associated with mortality in TA. We developed a simple and useful prognosis score to identify patients at risk for vascular complication and death. Disclosure of Interest: None declared